Alien Identities : Exploring Differences in Film and Fiction. - Whelehan, Imelda (Film/fiction ;, 1999)
A lively reexamination of the 'alien' as metaphor in film and fiction. Wide-ranging case studies include Dracula from Stoker to Coppola; British spy television series such as The Prisoner; and the work of H.G. Wells.